2007
DOI: 10.1111/j.1469-8137.2007.02281.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversification of phytochrome contributions to germination as a function of seed‐maturation environment

Abstract: Summary• Environmental conditions during seed maturation influence germination, but the genetic basis of maternal environmental effects on germination is virtually unknown.• Using single and multiple mutants of phytochromes, it is shown here that different phytochromes contributed to germination differently, depending on seed-maturation conditions.• Arabidopsis thaliana wild-type seeds that were matured under cool temperatures were intensely dormant compared with seeds matured at warmer temperature, and this d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
102
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(110 citation statements)
references
References 70 publications
8
102
0
Order By: Relevance
“…Arabidopsis seed primary dormancy is promoted by low-temperature conditions during seed development (23)(24)(25). Low temperature also increases seed dormancy in wheat and this correlates with an increase in Ta-MFT gene expression (29).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arabidopsis seed primary dormancy is promoted by low-temperature conditions during seed development (23)(24)(25). Low temperature also increases seed dormancy in wheat and this correlates with an increase in Ta-MFT gene expression (29).…”
Section: Resultsmentioning
confidence: 99%
“…Environmental conditions during seed set influence dormancy status. For example, low temperature conditions result in increased primary dormancy of mature Arabidopsis seeds (23)(24)(25) by inducing expression of genes associated with dormancy and influencing ABA and GA levels (24).…”
mentioning
confidence: 99%
“…Further evidence that the contributions of individual phytochromes are environmentally dependent comes from investigation of the effects of photoperiod and temperature on germination. These studies revealed a role for phyD in breaking cool-induced seed dormancy and in mediating the effects of photoperiod during seed maturation (Donohue et al, 2007). They further revealed that phyD is important in seed germination when seeds were matured (Dechaine et al, 2009) or imbibed (Heschel et al, 2008) under high temperatures, whereas phyE was important when seeds were imbibed in high temperatures followed by low temperatures (Heschel et al, 2008) or when matured under high temperatures (Dechaine et al, 2009).…”
Section: Additional Phytochromes: An Expanded Role For the Phytochrommentioning
confidence: 88%
“…Previous work has shown that lowering seed maturation temperatures induces high levels of dormancy in rapid cycling Arabidopsis ecotypes (Schmuths et al, 2006;Donohue et al, 2008;Chiang et al, 2009) as well as other species (Fenner, 1991;Gu et al, 2006). We confirmed that this was indeed a dormancy phenomenon by stimulating high levels of germination in seeds matured at low temperatures by applying multiple dormancy breaking treatments or by removing coat-imposed dormancy by nicking the seed coat (see Supplemental Figure 1A online) and by showing that embryo and seed coat morphology was normal in seeds developed at 108C (see Supplemental Figures 1B and 1C online).…”
Section: Identification Of Temperature-dependent Transcripts In Maturmentioning
confidence: 99%
“…During seed maturation, the level of dormancy is highly dependent on the prevailing environmental conditions with low temperatures and to a lesser extent short photoperiods, inducing high levels of dormancy and modifying the cold responsiveness of germination (Munir et al, 2001;Schmuths et al, 2006). Genetic influences on the induction of strong primary dormancy by low seed maturation temperatures have been uncovered, with roles for both phytochrome and FLC having been proposed (Donohue et al, 2008;Chiang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%